Overlap between Rothmund-Thomson and Baller-Gerold syndrome. - Rabba, S.; Hali, F.; Chiheb, S. (European Journal of Pediatric Dermatology, 2022)
Congenital poikiloderma is a rare, multisystem condition with onset in early childhood, present in numerous inherited skin disorders. Here we present a 7-year-old boy with a polymalformative syndrome associated with poikiloderma. The complex clinical data led to the diagnosis of an intermediate phenotype between Rothmund-Thomson (RTS) and Baller-Gerold (BGS) syndromes.